Unveiling Student Perspectives: Challenges and Insights on the Ordinary Level Examination - Ellippuli Arachchige Champika Nishanthi Perera; Loku Waduge Ransika De Alwis; Kahengoda Mudiyanselage Niranga Thanuja Kumari Bandara (Journal of Research in Education and Pedagogy, 2026)
The Ordinary Level (O/L) examination in Sri Lanka plays a crucial role in shaping students’ academic progression and career opportunities. This study investigates students’ perceptions of O/L exam questions, focusing on question difficulty, time management, question type preferences, and the impact of tuition classes. A mixed-methods approach was employed, using quantitative data from a sample of 318 students through descriptive and inferential statistics, alongside qualitative insights from thematic analysis. Results show that 32% of students faced difficulties with unclear questions, negatively affecting their confidence and performance. A significant correlation was found between tuition attendance and increased exam confidence, with 95% of students attributing improved preparedness to supplementary education. However, this also raises concerns about equity, as access to tuition varies by gender and socio-economic background. Time management was a major challenge, as 34% of students reported running out of time during exams. Additionally, 65% of students preferred long-answer questions, which allowed for more in-depth expression, while 60% found multiple-choice and structured questions challenging. The study highlights the need for greater clarity in exam questions, equal access to preparatory resources, and integration of time management training in school curricula. These findings emphasize the urgency of reforming the assessment system to ensure fairness, reduce stress, and better align with students’ learning needs and abilities.